Novel Approaches to the Measurement of flavour-related Properties: A Brief Overview and Future Prospects - Hughes, Paul (BrewingScience, 2010)
The challenges of relating analytical data to sensory evaluation are well-known, and may be attributed to recognised sensory biases and interactions (matrix-effects) that influence the sensory activity of flavour attributes. One approach to obviating these difficulties is to attempt to mimic sensory detection mechanisms to determine the activity of flavour attributes. In this short paper, two examples are given. Firstly, the feasibility of determining beer bitterness by exploiting the lipophilicity of hop bitter acids and measuring changes in pH across a model membrane. Secondly, the derivation of a measure of astringency by observing the binding of beer polyphenol complements to an appropriate protein. Whilst such an approach needs much fine-tuning and benchmarking against existing analytical and sensory tests, it nonetheless offers an alternative strategy for enhancing the predictiveness of beer flavour based on analytical measures.